Loo, Gomu and the British – an episode from early colonial Nigeria - Adelberger, Jörg (AAeO - Afrikanistik-Aegyptologie-Online, 2018)
Loo and Gomu are two small ethnic groups living in the Muri Mountains of Northern Nigeria. In the early British colonial era, such "pagan" groups were brought under administrative control by military means, at times with devastating results. New sources – a private letter by a young colonial officer as well as locally recorded songs - make it possible to present such an incident more accurately than before.